The German apprenticeship system : institutional frameworks and labour market performance - Franz, Wolfgang [Verfasser]; Soskice, David [Verfasser] (My University, 1994)
"The German apprenticeship training system is an anomaly in the standard world of labour economics. A large percentage of German firms voluntarily train apprentices to a high skill level even though economic theory suggests that these costs should be born by the trainees. We develop a formal 'lemon model' of apprenticeship training to account for the German case. In highly specialized and diversified production processes, the costs to firms of training apprentices can be less than the costs of training external hires in company-specific skills, especially when it is difficult for firms to measure the quality of external hires. Trainees would find it difficult to signal their quality to potential employers. Empirical evidence is presented to support this argument. We suggest that the German labour market institutional environment of work organisation and wage bargaining ecourages the development of such an apprenticeship training system." (author's abstract, IAB-Doku) ((en)) In dem Papier wird ein formales "Versager"-Modell der Lehrlingsausbildung entwickelt, um das deutsche System zu erklären. Es wird dargelegt, dass das arbeitsmarktrelevante Institutionengefüge, das Einfluss auf das Beschäftigungssystem hat, und das Tarifverhandlungssystem Deutschlands die Entwicklung dieses spezifischen Ausbildungssystems begünstigen. Dazu wird auf Gründe eingegangen, die vor allem Grossbetriebe dazu veranlassen, freiwillig und auf eigene Kosten Lehrlinge zu Facharbeitern auszubilden, statt Kosten des Anlernens extern angeworbener Mitarbeiter zu übernehmen. Qualifikationsermittlung und -nachweis spielen dabei eine Rolle. (IAB2)
Keywords: G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; G 1.2.3 Qualifikationsentwicklungen; L 7 Prüfungen; G 2.3.1 Arbeitsteilung & -organisation; G 2.3.5 Wirtschaftsstrukturwandel; S 4 Kosten & Finanzierung; P 2.4 Facharbeiter / Gesellen; S 4.3.6 Human Capital; G 1.3.3.1 Qualifikationsverwertung; Betriebliche Berufsausbildung; Berufsbildungssystem; Qualifikationsvermittlung; Qualifikationsnachweis; Arbeitsorganisation; Tarifverhandlungen; Struktur; Kosten; Facharbeiter; Angelernter; Humankapital; Ausbildungsinvestition; Qualifikationsverwertung; Quantitative Angaben